Purification and characterization of α-galactosidase from Aspergillus niger v. Tiegh RM48 - XU Yao-xing; LI Yan-li; LIU Yong; XU Shao-chun; YAO Xiao-hong (浙江大学学报. 农业与生命科学版)
An extracellular α-galactosidase from Aspergillus niger v. Tiegh RM48 was purified to apparent homogeneity by ammonium sulfate (80% saturation) precipitation, Phenyl Sepharose CL-4B hydrophobic column chromatography and Sephadex G-100 filtration chromatography. The specific activity of the enzyme was increased approximately 103-fold, from 26.29 IU·mg-1 protein to 2722.3 IU. mg-1 protein. The molecular mass of the purified enzyme as determined by SDS-PAGE was 108 kDa. The optimum pH and temperature of this α-galactosidase were pH 4.5 and 60 ℃, respectively. The enzyme was stable between pH 3.0 and pH 6.0, however, its activity was inhibited by all tested metal ions. α-Galactosidase activity was strongly inhibited by Cu2+, Fe2+ and moderately inhibited by Li2+, Zn2+, Mn2+, K+, Na+, Ca2+, Mg2+ and Co2+. Kinetic studies of the α-galactosidase showed that the Km and the Vmax for 4-nitrophenyl-α-D-galactopyranoside (pNPG) were 7.37 mmol·L-1 and 5618 IU· mg-1·min-1, respectively. The N-terminal amino acids sequence of the α-galactosidase protein was determined as DEKAYSPCYY, no evidence showed the apparent sequence similarity between this enzyme and any other α-galactosidase listed in the database.